The relationship between characteristics of nursing performance and years of experience in nurses with high emotional intelligence. Issue 6 (8th April 2014) - Fujino, Yuriko; Tanaka, Michiko; Yonemitsu, Yoshikazu; Kawamoto, Rieko
Abstract : The aim of this study was to elucidate characteristics of nursing performance among nurses with high emotional intelligence (EI) and examine the influence of years of experience on nursing performance and EI. A survey, including The Emotional Intelligence Scale and the Six‐Dimension Scale of Nursing Performance, was administered to 1395 nurses working at general hospitals in Japan from November 2010 to March 2011. We received 1045 responses (76% response rate). There was a significant positive correlation between EI and nursing performance. Nurses with high EI reported more professional development activities, suggesting that they continue learning, attain licenses and actively improve their nursing skills. High‐performing nurses had high situational abilities and showed improved nursing performance with experience. However, nurses with low situational abilities demonstrated no improvement in nursing performance related to experience. EI involves skills that can be acquired from training. Therefore, educational programmes to improve EI could improve nursing performance.